2022
DOI: 10.1021/acs.analchem.1c04823
|View full text |Cite
|
Sign up to set email alerts
|

trans-4-Fluoro-l-proline: A Sensitive 19F NMR Probe for the Rapid Simultaneous Enantiomeric Analysis of Multicomponent Amines

Abstract: Simultaneous enantiomeric analysis is especially important for medicine, food security, and life science. Chiral analysis of multicomponent amine mixtures still faces many challenges. Here, our work demonstrates for the first time that a novel chiral derivatizing agent CDApro based on trans-4-fluoro-l-proline (trans4Fpro) has been successfully used for the rapid simultaneous analysis of 22 chiral nonamino acid (non-AA) amines, multicomponent l/d-AAs, or mirror-image dipeptides in a mixture, as well as amines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…In addition, the chemical shifts are generally concentration-dependent due to weak interactions between amino acids and sensors. The chemical shift differences of the enantiomeric amino acids encoded in the chiral 19 F NMR tag with a bandwidth of 2.8 ppm is also larger than the recent chiral 19 F probe of a trans-4fluoro-L-proline derivative with a range of 0.6 ppm, 37 which shows high performance in discriminating the chiral amines in the organic solvent. The results indicate the spatial distance between the stereogenic center containing the 19 F reporter, and the chiral center of amino acids is a key factor in the discrimination of chiral molecules by 19 F NMR.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, the chemical shifts are generally concentration-dependent due to weak interactions between amino acids and sensors. The chemical shift differences of the enantiomeric amino acids encoded in the chiral 19 F NMR tag with a bandwidth of 2.8 ppm is also larger than the recent chiral 19 F probe of a trans-4fluoro-L-proline derivative with a range of 0.6 ppm, 37 which shows high performance in discriminating the chiral amines in the organic solvent. The results indicate the spatial distance between the stereogenic center containing the 19 F reporter, and the chiral center of amino acids is a key factor in the discrimination of chiral molecules by 19 F NMR.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…A just-accepted report uses a chiral 19 F probe in the formation of Schiff base products with the amino groups in organic solvents to quantify the chiral amines. 37 The complete transformation of amines to Schiff base products and the stability of Schiff base complexes in aqueous solution remains elusive. The previous work showed that qualitative and quantitative analyses of L-amino acids in biofluids by a reactive 19 F tag are feasible in aqueous solution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In our previous work, we found the influence of different solvents on the enantiodifference values of diastereoisomers. 2 Moreover, the resolution of 19 F NMR spectroscopy of a mixture solution was also assuredly solvent-dependent. 15,16 This is maybe due to the hydrogen bonds between nitrogen atoms and solvent molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…NMR-active isotope 19 F nuclei with 100% natural abundance exhibit a wide chemical shift range (∼400 ppm), which is exquisitely sensitive to the electronic microenvironment . These merits make 19 F NMR incredibly useful in the fields of analytical chemistry and chemical biology, such as the analysis of a complex multicomponent mixture, quantification of hydrogen bonds, and the conformational investigation of proteins or nucleic acids. …”
Section: Introductionmentioning
confidence: 99%